Grass Carp Follisatin: Molecular Cloning, Functional Characterization, Dopamine D1 Regulation at Pituitary Level, and Implication in Growth Hormone Regulation - Fung, Roger S. K.; Jin, Bai; He, Mulan; Yuen, Karen W. Y.; Wong, Anderson O. L. (Frontiers in Endocrinology, 2017)
Activin is involved in pituitary hormone regulation and its pituitary actions can be nullified by local production of its binding protein follistatin. In our recent study with grass carp, local release of growth hormone (GH) was shown to induce activin expression at pituitary level, which in turn could exert an intrapituitary feedback to inhibit GH synthesis and secretion. To further examine the activin/follistatin system in the carp pituitary, grass carp follistatin was cloned and confirmed to be single-copy gene widely expressed at tissue level. At the pituitary level, follistatin signals could be located in carp somatotrophs, gonadotrophs and lactotrophs. Functional expression also revealed that carp follistatin was effective in neutralizing activin’s action in stimulating target promoter with activin-responsive elements. In grass carp pituitary cells, follistatin co-treatment was found to revert activin inhibition on GH mRNA expression. Meanwhile, follistatin mRNA levels could be up-regulated by local production of activin but the opposite was true for dopaminergic activation with dopamine or its agonist apomorphine. Since GH stimulation by dopamine via pituitary D1 receptor is well-documented in fish models, the receptor specificity for follistatin regulation by dopamine was also investigated. Using a pharmacological approach, the inhibitory effect of dopamine on follistatin gene expression was confirmed to be mediated by pituitary D1 but not D2 receptor. Furthermore, activation of D1 receptor by the D1-specific agonist SKF77434 was also effective in blocking follistatin mRNA expression induced by activin and GH treatment both in carp pituitary cells as well as in carp somatotrophs enriched by density gradient centrifugation. These results, as a whole, suggest that activin can interact with dopaminergic input from the hypothalamus to regulate follistatin expression in carp pituitary, which may contribute to GH regulation by activin/follistatin system via autocrine/paracrine mechanisms.